The use of the HEC-RAS model to evaluate the pattern of sedimentation variations in areas of the Talar river - fateme hashemi; Ali Shahnazari; Andersen Mathias Neumann (تحقیقات کاربردی علوم جغرافیایی)
The catchment area of the Talar River in Mazandaran Province is subject to annual flooding events that facilitate the transport of substantial quantities of silt. To investigate sediment transport dynamics within this watershed, samples were collected at five designated sections along an 11-kilometer segment of the Talar River. The sampling intervals were delineated as follows: 24.7–22.4 km, 18.2–20.5 km, 17.5–18 km, 16.75–17.5 km, and 11.5–16.75 km, measured from the urban area of Malakala-Najjarkala to Arab Roshan, with all distances calculated from the shoreline. This study aimed to analyze sedimentation and erosion patterns over a five-year period (2016–2021) employing the HEC-RAS model. Sediment transport and volume were assessed based on long-term data obtained from the Kiakla hydrometric station, with a specific focus on flood conditions associated with return periods of 2, 10, 25, 50, and 100 years. The findings indicate that the cumulative sediment input at the beginning of the monitored section is 0.9 million tonnes lower than the total sediment at the end. The river exhibits a pronounced tendency towards erosion. In the first section (22.4–24.7 km), the mean sediment height is 11 cm, accompanied by significant sedimentation totaling 6 million tonnes. The second section reflects an approximate deposition of 1 million tonnes. The third section demonstrates a relatively stable sediment pattern. In the fourth section, the conditions for erosion—both in terms of depth and volume—are deemed unsuitable for sediment harvesting. The fifth section (11.5–16.75 km) records erosion amounting to approximately 8.3 million tonnes, with height variations ranging from 10 to 20 cm. Under these circumstances, sediment removal is impractical; However, the implementation of flood management strategies and river engineering interventions is strongly recommended.